ADTKD-UMOD in a girl with a de novo mutation: A case report - Li, Meng-shi; Li, Yang; Jiang, Lei; Song, Zhuo-ran; Yu, Xiao-juan; Wang, Hui; Ren, Ya-li; Wang, Su-xia; Zhou, Xu-jie; Yang, Li; Zhang, Hong (Frontiers in Medicine, 2022)
Autosomal dominant tubulointerstitial kidney disease due to UMOD mutations (ADTKD-UMOD) is a rare condition associated with high variability in the age of end-stage kidney disease (ESKD). An autosomal dominant inheritance is the general rule, but de novo UMOD mutations have been reported. It was reported that the median age of ESKD was 47 years (18-87 years) and men were at a much higher risk of progression to ESKD. Here, we reported a 13-year-old young girl with unexplained chronic kidney disease (CKD) (elevated serum creatine) and no positive family history. Nonspecific clinical and histological manifestations and the absence of evidence for kidney disease of other etiology raised strong suspicion for ADTKD. Trio whole-exome sequencing confirmed that she carried a de novo heterozygous mutation c.280T>C (p.Cys94Arg) in the UMOD gene. The functional significance of the novel mutation was supported by a structural biology approach. With no targeted therapy, she was treated as CKD and followed up regularly. The case underscores the clinical importance of a gene-based unifying terminology help to identify under-recognized causes of CKD, and it demonstrates the value of whole-exome sequencing in unsolved CKD.